Transcription Factors Active in the Anterior Blastema of Schmidtea mediterranea - Yoko Suzuki-Horiuchi; Henning Schmitz; Carlotta Barlassina; David Eccles; Martina Sinn; Claudia Ortmeier; Sören Moritz; Luca Gentile (Biomolecules, 2021)
Regeneration, the restoration of body parts after injury, is quite widespread in the animal kingdom. Species from virtually all Phyla possess regenerative abilities. Human beings, however, are poor regenerators. Yet, the progress of knowledge and technology in the fields of bioengineering, stem cells, and regenerative biology have fostered major advancements in regenerative medical treatments, which aim to regenerate tissues and organs and restore function. Human induced pluripotent stem cells can differentiate into any cell type of the body; however, the structural and cellular complexity of the human tissues, together with the inability of our adult body to control pluripotency, require a better mechanistic understanding. Planarians, with their capacity to regenerate lost body parts thanks to the presence of adult pluripotent stem cells could help providing such an understanding. In this paper, we used a top-down approach to shortlist blastema transcription factors (TFs) active during anterior regeneration. We found 44 TFs—31 of which are novel in planarian—that are expressed in the regenerating blastema. We analyzed the function of half of them and found that they play a role in the regeneration of anterior structures, like the anterior organizer, the positional instruction muscle cells, the brain, the photoreceptor, the intestine. Our findings revealed a glimpse of the complexity of the transcriptional network governing anterior regeneration in planarians, confirming that this animal model is the perfect playground to study in vivo how pluripotency copes with adulthood.